2015
DOI: 10.1093/iwc/iwv028
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Reactions to Point-Light Display Animations

Abstract: Emotional reactions to basic, artificial, yet carefully controllable point-light displays (PLDs) were investigated with ratings of valence, arousal, approachability, and dominance. PLDs were varied by movement location (upper and lower) and intensity (10°, 20°, and 30° angular change) for angular upward and downward movements. Half of participants (N = 28) were told that PLDs were related to face while to other half nothing was hinted. Results showed that 20° and 30° angle lower location upward movements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Each channel contributes important, or even necessary, signals. Research in HCI has attempted to use visual [30] and haptic/tactile feedback [20,[25][26][27]35] to convey the emotional state of another but, in general, these channels have been studied individually, with few multimodal approaches. Individual channels currently do not seem capable of conveying a wide range of emotions by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Each channel contributes important, or even necessary, signals. Research in HCI has attempted to use visual [30] and haptic/tactile feedback [20,[25][26][27]35] to convey the emotional state of another but, in general, these channels have been studied individually, with few multimodal approaches. Individual channels currently do not seem capable of conveying a wide range of emotions by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Outside of emoji ambiguity [26], research has looked at minimalist or abstract visual feedback designs, leveraging correlates of facial activity [44] or inherent psychological associations of colour to affective judgements [1,30,42,45]. Research has also identified hedonic perceptions of shape and contour, finding that people have a consistent preference for curved over pointed objects [7,30], possibly due to the inherent "threat" of sharp objects [8] (see summary in [51]).…”
Section: Visual Affective Feedbackmentioning
confidence: 99%
“…Research in HCI has looked at how certain individual modalities can convey affective information, including thermal feedback [33,34,49], vibration [27,36,53], force feedback [6,37,52] and abstract visual displays [43,44,51]. Unfortunately, research shows that the individual modalities are only capable of conveying a limited range of emotional meaning by themselves.…”
Section: Introductionmentioning
confidence: 99%